Peranan Program Jaminan Kesehatan Nasional (JKN) Dalam Mendorong Sustainable Development Goals (SDGs) di Indonesia - Nurhalimah Sitorus; Yusrizal, Yusrizal; Nasution, Juliana (Masyarakat Ekonomi Syariah Bogor, 2024)
The National Health Insurance has received great attention in the Sustainable Development Goals, where one of the main targets is to guarantee a healthy life and promote welfare for all people at all ages or later called Universal Health Coverage (UHC). The National Health Insurance is a social security program based on Law Number 40 of 2004 which aims to provide comprehensive health insurance coverage for every Indonesian so that Indonesians can live healthy, productive and prosperous lives. Whereas Universal Health Coverage is a health system that ensures that every citizen in the population has equitable access to quality promotive, preventive, curative and rehabilitative health services at affordable costs. In this study, in its implementation, there was an increase in the Community Health Development Index which was marked by an increase in health service efforts with cross-sector, central and regional synergy towards achieving Universal Health Coverage. The problem found in this study is that there are still many problems found regarding mothers, babies and toddlers. The nutritional status of the people who have a double burden, as well as problems regarding the quality and access to basic and referral health services which include fulfilling the conditions and facilities for basic and referral health services, fulfilling the availability of facilities and infrastructure for health service facilities both medical and non-medical, and not yet covering guarantee services national health as a whole. The purpose of this study was to find out the planning for the implementation of the National Health Insurance (JKN) program in Encouraging Sustainable Development Goals (SDGs) in Indonesia, especially in Medan City. This research is a descriptive qualitative research. The process of monitoring and evaluating the implementation of activities is carried out according to their duties and functions and in accordance with the procedures and provisions of the 1945 Constitution, Law Number 40 of 2004 concerning the National Social Security System Keywords: Role, National Health Insurance, SDGs